2010
DOI: 10.1038/cdd.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

Primate-specific RFPL1 gene controls cell-cycle progression through cyclin B1/Cdc2 degradation

Abstract: Ret finger protein-like 1 (RFPL1) is a primate-specific target gene of Pax6, a key transcription factor for pancreas, eye and neocortex development. However, its cellular activity remains elusive. In this article, we report that Pax6-elicited expression of the human (h)RFPL1 gene in HeLa cells can be enhanced by in vivo p53 binding to its promoter and therefore investigated the hypothesis that hRFPL1 regulates cell-cycle progression. Upon expression in these cells, hRFPL1 decreased cell number through a kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The primary substrate of Cdc25A is cyclin-dependent kinase 2 which allows cell cycle progression through the G 1 /S checkpoint when active. Our data indicated that expression levels of Cdc25A, Cdc2 and P-Cdc2 were decreased, similar to previous studies (31)(32)(33).…”
Section: Discussionsupporting
confidence: 92%
“…The primary substrate of Cdc25A is cyclin-dependent kinase 2 which allows cell cycle progression through the G 1 /S checkpoint when active. Our data indicated that expression levels of Cdc25A, Cdc2 and P-Cdc2 were decreased, similar to previous studies (31)(32)(33).…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have revealed hRFPL1, 2, 3 play a vital role in neurogenesis [ 34 , 35 ]. RFPL1 may participate in cell differentiation and cell-cycle regulation [ 36 ]. RFPL3 might enhance significantly the activity of human immunodeficiency virus, type 1 (HIV-1) PIC integration in infected cells in vitro [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HG-U133 Plus 2.0 microarray is widely used to profile genome-wide gene expression, which proved abundant resource for data mining. The raw CEL files were downloaded and quantile normalized and background adjusted using Robust Multichip Average (RMA, Windows Version) [33, 34]. After normalization, expression value of each probe was obtained.…”
Section: Methodsmentioning
confidence: 99%